2004
DOI: 10.1111/j.1365-2893.2004.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the putative HCV‐E2 CD81 binding regions and correlation with cell surface CD81 expression

Abstract: The hepatitis C virus (HCV) envelope (E)2 protein interacts with the cellular receptor CD81 leading to modulation of B and T cell function. Recently, a higher binding affinity of subtype 1a in comparison with 1b derived E2 proteins for CD81 in vitro was described. The importance of mutations within the putative CD81 binding regions of different HCV geno-/subtypes in correlation with CD81 expression is unknown. In the present study, CD81 expression on blood lymphocytes of patients with chronic hepatitis C infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The factors responsible for HCV enrichment in PBL preparations from cryoglobulinaemic patients are unknown, but may be related to the higher density and/or genetic polymorphism of the putative (co)receptor gene for HCV binding [37,38]. The connection between HCV cells enrichment and cryoglobulin production is also unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The factors responsible for HCV enrichment in PBL preparations from cryoglobulinaemic patients are unknown, but may be related to the higher density and/or genetic polymorphism of the putative (co)receptor gene for HCV binding [37,38]. The connection between HCV cells enrichment and cryoglobulin production is also unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it appears that formation of the CD81-E2 complex does not necessarily confer susceptibility to the virus. It has also been observed that different HCV strains utilize CD81 to different extents (70,94,131); E2 subtype 1b, for instance, shows a lower binding affinity to CD81-LEL than E2 subtype 1a. The CD81-LEL Phe186Leu mutation has been shown to abolish the binding of CD81 LEL to soluble E2 strain H but not to strain Con 1, even though this mutation has no effect on the ability of transfected HepG2 cells to support infection by pseudotype viruses expressing either Con 1 or strain H E2 (175).…”
Section: Flaviviruses: Hcv and Cd81mentioning
confidence: 99%
“…MC patients are distinctly characterized by higher levels of cell-associated viral load, because a significant enrichment of HCV RNA in PBL has been demonstrated [61]. This peculiar feature may be considered as the result of a higher density [62] and/or polymorphism of receptor genes [63, 64], whereas direct infection and replication of HCV in B cells may promote lymphocyte proliferation [65]. …”
Section: Hcv Infection and Lymphoid Cellsmentioning
confidence: 99%